Palmoplantar keratoderma: An unusual manifestation of hypohydrotic ectodermic dysplasia. Issue 3 (13th March 2022) - Abdelli, Wissal; Souissi, Asmahen; Alaoui, Fatima; Sassi, Wiem; Chelly, Ines; Haouat, Slim; Mokni, Mourad
Abstract: Rapp–Hodgkin syndrome (RHS) is a rare condition that is characterized by ectodermal dysplasia and palatal abnormalities. Palmoplantar keratoderma (PPK) is an unusual manifestation of hidrotic ED. Ulcerations on the palms are also not common in RHS. We describe a 15‐year‐old boy who has RHS associated with PPK. Abstract : Ulcerations on the palms are not common in RHS. Keratoderma is also considered an uncommon manifestation of hidrotic ectodermal dysplasia. Dermatologists must be aware of these conditions.